EDUCATIONAL E-ENVIRONMENT THROUGH ENGLISH VOCABULARY DEVELOPMENT - Makhachashvili, Rusudan (Електронне наукове фахове видання “ВІДКРИТЕ ОСВІТНЄ Е-СЕРЕДОВИЩЕ СУЧАСНОГО УНІВЕРСИТЕТУ”, 2016)
The study objective is the investigation of innovative linguophilosophic aspects of English vocabulary development in the sphere of cybertechnologies. Research methodology is based upon the supposition of the cyberspace-related word-stock terminological nature. The dual systematization character of terminology determined the analysis of both linguistic and external (ontological, anthropological, social) paradigmatic parameters of English cybervocabulary. Paradigmatic parameters of English computer terminology are featured from the following perspectives: perception of basic dimensions of cyber-reality (“space” and “time”) and anthropologic categorization of cyber-reality, thus both the anthropocentric and the sociocentric paradigmatics of English cyber vocabulary are reflected. The “artificial” digital environment is acquiring more independence as far as the “parent” reality is concerned and establishes the basis for being considered a separate metalingual entity. Hence, one of the prior ways fundamental ontological categories are exposed within cyberspace being through the language (precisely by means of contributing to the modern English vocabulary), we may assume the natural language itself to find its realization in ontological manner.